2020
DOI: 10.3390/f11050585
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration Dynamics Following the Formation of Understory Gaps in a Slovakian Beech Virgin Forest

Abstract: The frequency and size of canopy gaps largely determine light transmission to lower canopy strata, controlling structuring processes in the understory. However, quantitative data from temperate virgin forests on the structure of regeneration in gaps and its dynamics over time are scarce. We studied the structure and height growth of tree regeneration by means of sapling density, shoot length growth and cumulative biomass in 17 understory gaps (29 to 931 m2 in size) in a Slovakian beech (Fagus sylvatica L.) vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 68 publications
4
14
0
Order By: Relevance
“…Mountford et al [86], in a managed beechwood in southern England, and Gálhidy et al [87], in a temperate deciduous forest found more prolific beech regeneration in small and medium gaps. Our results are also consistent with previous studies [32,88], reporting that European beech grew optimally in gap openings minor than 500 m 2 . In short, our result highlighted that in the small and medium gaps, the combination of moderate levels of diffuse light and relatively low levels of direct light created more favorable conditions in soil moisture and nutrients, particularly for nitrogen and potassium whose presence is important for beech natural regeneration (species shade tolerant), confirming previous observations of other authors [58,89,90].…”
Section: Discussionsupporting
confidence: 93%
“…Mountford et al [86], in a managed beechwood in southern England, and Gálhidy et al [87], in a temperate deciduous forest found more prolific beech regeneration in small and medium gaps. Our results are also consistent with previous studies [32,88], reporting that European beech grew optimally in gap openings minor than 500 m 2 . In short, our result highlighted that in the small and medium gaps, the combination of moderate levels of diffuse light and relatively low levels of direct light created more favorable conditions in soil moisture and nutrients, particularly for nitrogen and potassium whose presence is important for beech natural regeneration (species shade tolerant), confirming previous observations of other authors [58,89,90].…”
Section: Discussionsupporting
confidence: 93%
“…Non-pioneer light demanding (NPLD) recorded the highest number of 38 species, followed by pioneers with 30 species, whereas shade-tolerant attained the lowest representatives of 17 species in regenerated species composition. This finding supports the long-standing notion that light-tolerant species prefer open space environments for optimum regeneration [5] while those environments normally impede regeneration of shadeadapted species [2]. Pioneers-Terminalia superba (frequency, regeneration density, relative density = 97, 774 trees/ha, 6.61%) and Daniella ogea (85, 678 trees/ha, 5.79%), NPLD-Mansonia altissima (75, 598 trees/ha, 5.11%), and Blighia sapida (70, 558 trees/ha, 4.77%), and shade-tolerant-Nesogordonia papaverifer (340, 2711 trees/ha, 23.16%), Celtis mildbraedii (188, 1499 trees/ha, 12.81%) and Baphia nitida (185, 1475 trees/ha, 12.60%) were the predominant tree species found almost in all gaps.…”
Section: Impact Of Gap Ecology On Species Composition and Diversitysupporting
confidence: 84%
“…Generally, canopy gaps influence forest regeneration cycles by offering local resource-rich niches for understory tree species [1]. Differences among tree species in establishment, germination, development, survival, growth, and canopy recruitment within gap sites explain the crucial role of canopy gaps in shaping forest composition [1,2]. This very important role of canopy gaps had been well documented in numerous gap regeneration studies conducted in temperate [3] and tropical [4] forest ecosystems.…”
Section: Introductionmentioning
confidence: 97%
“…This positive trend has already been confirmed by Olson and Wagner (2011), who attributed resource availability (i.e., light) in the disturbed environment as the major factor responsible for seedling regeneration. According to Feldmann et al (2020), light transmission to the lower strata influences structuring processes, including seedling regeneration. Logging creates a heterogeneous canopy with different microenvironments that differ in light intensity and different degrees of soil disturbance, advantageous for seedling regeneration (Duah-Gyamfi et al, 2014).…”
Section: The Influence Of Older Stand Structure On Seedling Regenerationmentioning
confidence: 99%